2022
DOI: 10.1002/ece3.9017
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of an invasive forest insect under current and future projected temperature regimes

Abstract: Temperature and its impact on fitness are fundamental for understanding range shifts and population dynamics under climate change. Geographic climate heterogeneity, behavioral and physiological plasticity, and thermal adaptation to local climates make predicting the responses of species to climate change complex. Using larvae from seven geographically distinct wild populations in the eastern United States of the non‐native forest pest Lymantria dispar dispar (L.), we conducted a simulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In contrast with the long‐term Hallmann et al study, our sampling only spanned 3 years, so it suggests that there are important regional differences in ecology (natural or anthropogenic) that are currently influencing insect biomass across North America. One possible explanation for the different responses is that there were different species in the regions we studied (i.e., community composition varies), but studies have also found that even within the same species there can be a local adaptation to temperature that influences population growth rates (e.g., Kingsolver et al, 2011; Porcelli et al, 2017), and therefore abundance and biomass (see also González‐Tokman et al, 2020; Walter et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the long‐term Hallmann et al study, our sampling only spanned 3 years, so it suggests that there are important regional differences in ecology (natural or anthropogenic) that are currently influencing insect biomass across North America. One possible explanation for the different responses is that there were different species in the regions we studied (i.e., community composition varies), but studies have also found that even within the same species there can be a local adaptation to temperature that influences population growth rates (e.g., Kingsolver et al, 2011; Porcelli et al, 2017), and therefore abundance and biomass (see also González‐Tokman et al, 2020; Walter et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that thermal adaptation along the invasion front (i.e. range margin) in addition to their preexisting phenotypic plasticity has fuelled their continued spread and expansion as they have encountered less favourable climates (Faske et al., 2019; Friedline et al., 2019; Thompson et al., 2017, 2021; Walter et al., 2022). However, since we have observed temperature‐related range contractions along the southern invasion front (Tobin et al., 2014), we may be observing the current limits of climate‐related plasticity and evolvability of L. d. dispar .…”
Section: Discussionmentioning
confidence: 99%
“…The cloned BtCAT amplicons were ligated into the pEASY-T1 vector (TransGen, Beijing, China) and transformed into Escherichia coli Trans1-T1 competent cells (TransGen) for final sequencing. Through sequencing data and genomic data analysis, the exon numbers (10) of BtCATs and the conserved structure of BtCATs were determined (Supporting Information, Fig. S1).…”
Section: Gene Cloningmentioning
confidence: 99%
“…Hightemperature or low-temperature environments can lead to physiological dysfunction and even direct death of insects, ultimately leading to the extinction of populations. 9,10 To maintain normal life activities, insects make a series of physiological metabolic adjustments in response to external temperature stress. [11][12][13] For example, bees sit motionless on the caps of brood cells and regulate the temperature of the brood nest by generating heat.…”
Section: Introductionmentioning
confidence: 99%